2008
DOI: 10.1007/s11243-008-9115-6
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the uninhibited and ethanol-inhibited CoO, Co2O3 and Ni2O3 catalyzed autoxidation of sulfur(IV) in alkaline medium

Abstract: For getting an insight into the mechanism of atmospheric autoxidation of sulfur(IV), the kinetics of this autoxidation reaction catalyzed by CoO, Co 2 O 3 and Ni 2 O 3 in buffered alkaline medium has been studied, and found to be defined by Eqs. I and II for catalysis by cobalt oxides and Ni 2 O 3 , respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…S(IV), were studied by following the decrease in the concentration of S(IV). This procedure was the same as that described by Brodizinsky et al [42] and subsequently used by us [43][44][45][46]. The reactions were conducted in 0.15 L Erlenmeyer flasks open to air, to allow the passage of atmospheric oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…S(IV), were studied by following the decrease in the concentration of S(IV). This procedure was the same as that described by Brodizinsky et al [42] and subsequently used by us [43][44][45][46]. The reactions were conducted in 0.15 L Erlenmeyer flasks open to air, to allow the passage of atmospheric oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…The high reactivity of Co/Cr surfaces toward oxygen plays a key role in technological applications, ranging from perpendicular magnetic recording media 10,11 to orthopedic implants 12 and heterogeneous catalysis. 13,14 In particular, Cr is one of the most established alloying elements for corrosion protection.…”
Section: Introductionmentioning
confidence: 99%
“…Prasad & Gupta et al [11,37] proposed a similar mechanism for the Co 2 O 3 and CoO catalysed autoxidation of SO 2 inhibited by formic acid and ethanol respectively, which lead to the same rate law. By comparing derived rate law with the experimental rate law we observe the similarity in these two.…”
Section: Hso H Somentioning
confidence: 95%
“…The rate of uncatalysed and Ag(I) catalysed reaction is decelerated by the addition of aniline in the present study. Gupta et al [37] reported that radical mechanism operate in those reaction in which the inhibition parameters lies 10 3 -10 4 In the present study the value of inhibition parameter for uncatalysed and Ag(I) catalysed autoxidation of S(IV) by anilineare found to be in the range 10 3 -10 4 These values are in the same range as reported by Gupta et al [37] This is strongly support the radical mechanism in the present case too based on the observed results. The free radical mechanism is very complex, the present work close to the experimental condition of Connick et al [38].…”
Section: Hso H Somentioning
confidence: 99%